Florae costaricensis subtribui Pleurothallidinis (Orchidaceae) prodromus II. Systematics of the Pleurothallis cardiothallis and P. phyllocardia Groups, and Other Related Groups of Pleurothallis with Large Vegetative Habit - Pupulin, Franco (2021)
We discuss a group of Pleurothallis species mostly characterized by plants relatively tall for the genus, with stems more than 20 cm long and fasciculate inflorescences produced above the leaf from a spathaceous, sometimes erect bract. We recognize 26 species and 4 natural hybrids in Costa Rica in this group of Pleurothallis, belonging to 4 informal assemblages of species, each one characterized by a unique set of vegetative, floral, and ecological features. This group, as well as its component units, is discussed as to its salient characteristics and internal relationships, underlying possible evolutionary trends. Diversity, general and floral ecology, color dimorphism, and natural hybridization are examined to address their systematic significance. We present a dichotomic key to the groups and the species discussed in this study, together with descriptions based on Costa Rican materials, and one or more line drawings or a Lankester Composite Dissection Plate when required for improved clarity. Also, we discuss their taxonomy and provide information on etymology, habitat, distribution, distinguishing features, and Costa Rican collections. Three species (P. callosa, P. longipetala, and P. mesopotamica), and three nothospecies (P. ×karremansiana, P. ×subversa, and P. ×parentis-certa) are described as new to science, discussed as to their affinities, and illustrated with photographs, composite digital plates, and ink drawings. Pleurothallis triangulabia is removed from the synonymy of P. phyllocardia, treated as a distinct species, and lectotypified. Pleurothallis anthurioides and P. maduroi are first recorded and documented for the flora of Costa Rica.